A comparison of the low temperature transcriptomes of two tomato genotypes that differ in freezing tolerance: Solanum lycopersicum and Solanum habrochaites - Chen, Hongyu (BMC Plant Biol, 2015)
BACKGROUND: Solanum lycopersicum and Solanum habrochaites are closely related plant species; however, their cold tolerance capacities are different. The wild species S. habrochaites is more cold tolerant than the cultivated species S. lycopersicum. RESULTS: The transcriptomes of S. lycopersicum and S. habrochaites leaf tissues under cold stress were studied using Illumina high-throughput RNA sequencing. The results showed that more than 200 million reads could be mapped to identify genes, microRNAs (miRNAs), and alternative splicing (AS) events to confirm the transcript abundance under cold stress. The results indicated that 21 % and 23 % of genes were differentially expressed in the cultivated and wild tomato species, respectively, and a series of changes in S. lycopersicum and S. habrochaites transcriptomes occur when plants are moved from warm to cold conditions. Moreover, the gene expression patterns for S. lycopersicum and S. habrochaites were dissimilar; however, there were some overlapping genes that were regulated by low temperature in both tomato species. An AS analysis identified 75,885 novel splice junctions among 172,910 total splice junctions, which suggested that the relative abundance of alternative intron isoforms in S. lycopersicum and S. habrochaites shifted significantly under cold stress. In addition, we identified 89 miRNA sequences that may regulate relevant target genes. Our data indicated that some miRNAs (e.g., miR159, miR319, and miR6022) play roles in the response to cold stress. CONCLUSIONS: Differences in gene expression, AS events, and miRNAs under cold stress may contribute to the observed differences in cold tolerance of these two tomato species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0521-6) contains supplementary material, which is available to authorized users.